2019
DOI: 10.1002/tcr.201800205
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances Utilized in the Recycling of Homogeneous Catalysis

Abstract: Homogeneous catalysts often show high activity and selectivity towards the various chemical transformations. Most of the transition metal‐based active catalysts are expensive, rare, and have strict regulations for their use in pharmaceutical products. Hence, there is a requirement to develop suitable technologies for the practical separation and recycling of metal complex catalysts along with the sustainability of the process. This review focuses on the recent techniques used for the catalyst separation, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 138 publications
(111 reference statements)
0
62
0
2
Order By: Relevance
“…Next, by considering the importance of recyclability of the catalyst [15] N‐DFNS‐700 was used to test the reusability at the optimized reaction condition. It was observed that this material showed potential recyclability up to five consecutive runs with minimal loss in its activity (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Next, by considering the importance of recyclability of the catalyst [15] N‐DFNS‐700 was used to test the reusability at the optimized reaction condition. It was observed that this material showed potential recyclability up to five consecutive runs with minimal loss in its activity (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…3 three shell layers of alginate amide containing Grubbs' catalyst. 4 reduced amount of enzyme (−60%). 5 five shell layers of alginate amide containing Grubbs' catalyst.…”
Section: Co-encapsulationmentioning
confidence: 99%
“…Sustainability in chemistry has been developing into an expanding and complex field due to increasing demand in recent years [1,2]. There are different approaches to address this topic such as using water as reaction medium [3], enabling catalyst recycling [4], implementing more sustainable reaction steps in synthesis routes or even starting from renewable resources and creating new synthesis routes [5]. Since chemical processes in industry often imply catalytic reaction steps, it is of major interest to develop new catalytic processes with catalysts that are highly selective, stable and catalyse reactions at mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In short, it is a soluble catalyst in a solution [119]. Homogeneous catalyst generally provides short reaction time and needs a few amounts of catalyst in the catalytic system owing to it can contact with reactant adequately compare to the heterogeneous catalyst [120]. Interestingly, the ligand 4-methyl-2-phenylaniline-derived oxalamide is tolerated in a broad range of functional groups, including amines, alcohols, amides, halides, esters, ketones, and nitriles, as well as several heterocycles (Scheme 40).…”
Section: Homogeneous Catalystmentioning
confidence: 99%